Proses Permohonan Penetapan Hakim Tentang Pengurusan Harta Bawaan Yang Diwarisi Dari Ibu Yang Telah Meninggal Terhadap Anak Di Bawah Umur Oleh Ayahnya (Studi Kasus di Pengadilan Negeri Surakarta) - Oktariani, Oki; , Nuswardhani, S.H.,S.U (2016)
The constraints of a husband who would take care of congenital treasure wife who had died on his son because the child is still a minor and thus require court permission to take care of it. This study aims to determine the consideration of the judge in determining the determination of civil upon the request of the management of assets innate property of the wife who had died by the husband against minors, to determine the legal consequences after the imposition of the determination of the maintenance of the property innate property of the wife who had died by the husband against children under age. The research method using normative juridical approach that is descriptive. Using this type of primary data and secondary data. Data collection techniques used through the study of literature, questionnaire and interview. By using descriptive qualitative data analysis. The results showed that the consideration of the judge looks at the evidence at trial, legal consequences for the parties in the hearing the applicant can prove petition, that the petition applicant is granted, the applicant is charged with responsibility for the management of assets innate property of children under age until the child is an adult.